2021
DOI: 10.18174/sesmo.2021a17895
|View full text |Cite
|
Sign up to set email alerts
|

Learning across disciplines in socio-environmental problem framing

Abstract: Modelling complex socio-environmental problems requires integration of knowledge across disparate fields of expertise. A key challenge is understanding how social learning across disciplines occurs in scientific research teams, in order that integrated knowledge is co-created. This article introduces a new framework for training researchers to integrate their knowledge across disciplines, based on current understanding of how inter- and transdisciplinary learning in research teams occurs. The framework was gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
3
11
0
Order By: Relevance
“…They describe an interdisciplinary program for PhD students who conduct individual PhD research in a specialized field while working in parallel in a cross-disciplinary team. Moreover, our findings stress the need to explicitly train students in competencies for interdisciplinarity, which requires not only acquiring knowledge about interdisciplinarity, but also gaining experience in interdisciplinarity to acquire skills (Bridle et al 2013;Pennington et al 2021), and reflection to develop an attitude that supports interdisciplinary teamwork (Parker 2010). To raise awareness of disciplinary differences that was quite commonly lacking in our cohort, as became clear from the students with naïve behaviour, one could use approaches such as the Toolbox dialogue method (Hubbs et al 2020), as applied by Kjellberg et al (2018) to support the development of interdisciplinary consciousness and by Pennington et al (2021) to expose differences in epistemological assumptions to aid interdisciplinary teamwork.…”
Section: Discussionmentioning
confidence: 76%
“…They describe an interdisciplinary program for PhD students who conduct individual PhD research in a specialized field while working in parallel in a cross-disciplinary team. Moreover, our findings stress the need to explicitly train students in competencies for interdisciplinarity, which requires not only acquiring knowledge about interdisciplinarity, but also gaining experience in interdisciplinarity to acquire skills (Bridle et al 2013;Pennington et al 2021), and reflection to develop an attitude that supports interdisciplinary teamwork (Parker 2010). To raise awareness of disciplinary differences that was quite commonly lacking in our cohort, as became clear from the students with naïve behaviour, one could use approaches such as the Toolbox dialogue method (Hubbs et al 2020), as applied by Kjellberg et al (2018) to support the development of interdisciplinary consciousness and by Pennington et al (2021) to expose differences in epistemological assumptions to aid interdisciplinary teamwork.…”
Section: Discussionmentioning
confidence: 76%
“…These fi ndings are in line with earlier fi ndings that emphasise the importance of learning inter-and transdisciplinarity through practice (e.g. Pennington et al, 2021). The involvement of teaching staff from a department specialised in inter-and transdisciplinary research and education enabled us to implement these strategies, echoing previous reports about the importance of teachers' abilities (Acevedo-Osorio et al, 2020;.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that learning to engage in inter-and transdisciplinarity can be achieved through doing and experiencing inter-and transdisciplinary collaboration in practice (e.g. Freeth & Caniglia, 2020;Pennington et al, 2021). Moreover, learning about inter-and transdisciplinarity from theory has also been reported to contribute to learning to engage in inter-and transdisciplinary learning (e.g.…”
Section: Learning To Engage In Inter-and Transdisciplinaritymentioning
confidence: 99%
See 1 more Smart Citation
“…This makes participatory modeling particularly flexible for bridging cross-disciplinary knowledge, ranging from problem conceptualization, assumed system components, and methodological approaches, the three categories of epistemological approach addressed in this paper. There are many examples of the process of co-creating model representations of socio-ecological systems [91]. These examples illustrate how both conceptual and computational models can be used to facilitate in-depth transdisciplinary discussions about appropriate resolutions, processes/dynamics that need to be represented, important system outputs, and system components [94,95].…”
Section: Suggestions For Future Researchmentioning
confidence: 99%